Data–rich description of a new genus of praying mantid egg parasitoids, Lasallegrion gen. n. (Hymenoptera: Torymidae: Podagrionini), with a re-examination of Podagrion species of Australia and New Caledonia. Issue 9 (18th March 2020) - Janšta, Petr; Delvare, Gérard; Baur, Hannes; Wipfler, Benjamin; Peters, Ralph S.
ABSTRACT: The genus Lasallegrion gen. n. is described, and three species, Lasallegrion koebelei (Crawford 1912 ), comb. n., Lasallegrion virescens (Strand 1911 ), comb. n., and Lasallegrion washingtoni (Girault 1915 ), comb. n., are redescribed and transferred to it. Podagrion holbeini Girault 1923, syn. n., and Podagrion metatarsum Girault 1929, syn. n., are synonymised here with Lasallegrion koebelei . Further, 14 species from Australia and New Caledonia are confirmed as belonging to Podagrion Spinola, 1811. The classic morphological approaches are combined with multivariate ratio analysis and molecular and additional morphological methods for (re-)descriptions. A comprehensive set of morphometric data, COI barcode sequences, a fully sequenced transcriptome and detailed µCT data are provided. An updated key to the Australasian genera of Podagrionini and to the Lasallegrion species is given. Additionally, we present some discussion on the collisions of the concepts of modern taxonomy, and the restrictions caused by poorly conditioned old type material.